Perancangan Sistem Monitoring Jaringan berbasis Web Server Terintegrasi Zabbix dan Notifikasi Telegram Pada PT Time Excelindo - Mochamad Rivan Ary Arsandi; Ari Syaripudin (CV. Multi Kreasi Media, 2024)
The development of Information Technology is growing rapidly, especially in the computer network sector. This makes information exchange happen very quickly, in minutes or even seconds. With the availability of the internet (interconnection network), the exchange and delivery of information is accelerating. An Internet Service Provider (ISP) is a company that provides internet services. Network administrator is the person responsible for managing the network. One of the network administrator's duties is to monitor network devices while in the office or outside the office. By using a webserver, the monitoring process can be done anywhere as long as it is connected to the internet and with network monitoring zabbix a network administrator can also monitor bandwidth usage in graphical form and generate data in real time. The zabbix server also uses realtime telegram notification alerts, making it easier for the technical team to handle troubleshooting.